"We have to be uncomfortable and creative": Reflections on the impacts of the COVID-19 pandemic on overdose prevention, harm reduction & homelessness advocacy in Philadelphia - Shoshana V. Aronowitz; Eden Engel-Rebitzer; Margaret Lowenstein; Zachary Meisel; Evan Anderson; Eugenia South (Elsevier, 2021)
The COVID-19 pandemic and ensuing service delivery interruptions had serious impacts on people who use drugs (PWUD) and people experiencing homelessness, including instability in the drug supply, decreased access to substance use disorder (SUD) treatment and harm reduction supplies, increased substance use and relapse due to stress and isolation, inability to properly isolate and quarantine without stable housing, and risk of COVID-19 spread in congregate living spaces. At the same time, many have noted a potential opportunity for rapid change in health, housing, and drug policy despite previous stagnation-referred to as a "punctuated equilibrium" by Baumgartner and Jones-in response to the pandemic. The pandemic forced some important policy interventions in the United States at both national and local levels, including eviction moratoriums and loosening of drug policy related to substance use treatment. However, to what extent some of these changes will be sustained past the current COVID-19 crisis is still unclear, as is how drug and housing related policy shifts have impacted the work of frontline overdose prevention, substance use treatment, and homelessness advocacy workers. In this qualitative study, we used semi-structured interviews to assess how Philadelphia's harm reduction advocates, community organizers, and SUD treatment clinicians have responded to the overdose and homelessness crises during COVID-19, and how they predict the pandemic and ensuing policy changes will impact the future of overdose prevention, harm reduction efforts, and homelessness advocacy. We interviewed 30 eligible participants during July and August 2020. The analysis of these data yielded three themes: 1/"None of it should be new to anybody": COVID-era issues impacting PWUD and people experiencing homelessness are extensions of existing problems; 2/"An opportunity to actually benefit in some way from this crisis": Possibility for innovation and improved care for PWUD and people experiencing homelessness; and 3/"Nothing we've tried has worked, so we have to be uncomfortable and creative": The uncertain path forward. Despite the many barriers that participants faced to promoting the health and well-being of marginalized communities during the pandemic, they also believed that the pandemic presented an important opportunity for positive policy change that has the potential to promote drug user health into the future, including a continuation of loosened federal restrictions on substance use disorder treatment, legalization of safe consumption spaces, safe supply of substances, and progressive, creative housing solutions.